IMPLEMENTASI PEMBELAJARAN BERBASIS SCIENCE, TECHNOLOGY, ENGINEERING, ART, MATHEMATIC (STEAM ) DARI BAHAN LOOSE PARTS UNTUK MEMBANGUN MERDEKA BELAJAR ANAK USIA DINI - Sefriyanti Sefriyanti (AS-SALAM, 2022)
This study aims to determine the implementation of STEAM-based learning from loose parts so that children are free to learn fun and according to children's interests. The research method used is descriptive qualitative phenomenological techniques according to what is happening or field facts. Data collection techniques through observation, documentation and interviews. Observations were made by looking directly at the learning process in the classroom supported by photo documentation of children's activities. The subjects of this study were group B aged 5-6 years in RA Azzahra Way Jepara, East Lampung. The data analysis technique uses Miles and Huberman's three-way theory, namely data reduction, data presentation and conclusion drawing. The results showed that the implementation of STEAM-based learning activities from loose parts material was applied through several stages, namely, first, applying various kinds of play invitations by utilizing materials and tools in the surrounding environment, both teachers provoking by providing open-ended questions to stimulate thinking patterns. children about what will be done in the process of learning activities, thirdly giving freedom to children to choose tools, materials and play activities according to children's interests.